A educação física na primeira fase do primeiro grau - Abreu, Denise Reis de Castro e (1978)
In order to develop our bases for the teaching methode of the 'Education for Movements' from kindergarten to 4th grade, we examined Piaget's theory on the development of intelligence. This bibliographical research was based on Law 5692 and on the National Physical Education (Act) Policy. 'Education for Movements', as we shall now call Physical Education, is considered a very efficient way of intelligence developing, physical aptitude and group relationships, the student's potentials for selffulfilment, and of preparing him for his sion and citizenship.